2020
DOI: 10.1177/1056789520950409
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural features effect on the evolution of cyclic damage for polycrystalline metals using a multiscale approach

Abstract: In the context of polycrystalline metals, the damage process analysis is generally restricted to surface of a sample containing some hundreds of grains, due to the inherent difficulties microstructural analysis. Determination of the grain size influence, misorientation and neighboring grains effect remains difficult with experimental studies. In this work, the influence of microstructural characteristics of polycrystalline metals on the evolution of the damage process under cyclic loading is investigated. On t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…In this paper, the damage models are divided into creep damage ( Dc) and fatigue damage ( Df) and each damage model is expressed as total damage ( D ) to consider the interaction effects in the creep-fatigue loading condition. The Lemaitre-Chaboche isotropic damage model for fatigue damage represents transangular defects that occur under cyclic loading (Bouchedjra et al., 2021; Doghri, 2013). In order to express the nonlinear softening behavior, a nonlinear term is added to the model.…”
Section: Formulation Of Chaboche Unified Elasto-viscoplastic Fatigue ...mentioning
confidence: 99%
“…In this paper, the damage models are divided into creep damage ( Dc) and fatigue damage ( Df) and each damage model is expressed as total damage ( D ) to consider the interaction effects in the creep-fatigue loading condition. The Lemaitre-Chaboche isotropic damage model for fatigue damage represents transangular defects that occur under cyclic loading (Bouchedjra et al., 2021; Doghri, 2013). In order to express the nonlinear softening behavior, a nonlinear term is added to the model.…”
Section: Formulation Of Chaboche Unified Elasto-viscoplastic Fatigue ...mentioning
confidence: 99%
“…Estimation of fatigue life, damage evolution, and remaining useful life has captured the attention of numerous studies (Ferreira et al., 2022; Hou et al., 2023; Huo et al., 2022; Santecchia et al., 2016). Research has demonstrated that the fatigue behavior of a material under cyclic loading can be influenced by a multitude of parameters (Bouchedjra et al., 2021; Nihei et al., 1986; Zhu et al., 2022) that tend to complicate the prediction of fatigue performance. Considerable efforts have been directed towards forecasting the remaining useful life for components experiencing fatigue loading (Gan et al., 2023; Kralovec and Schagerl, 2020), particularly in scenarios involving variable amplitude fatigue loading (Si-Jian et al., 2018; Zuo et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…From a macroscopic perspective, fatigue damage accumulates with the number of loading cycles, accompanied with the degradation of material properties (Liakat and Khonsari, 2014; Ye and Wang, 2001), the dissipation of elastoplastic energies (Morrow, 1986) and the evolution of fatigue crack systems (Bouchedjra et al., 2021; Ghammouri et al., 2011). Following these philosophy, numerous phenomenological damage models have been put forward over the past decades.…”
Section: Introductionmentioning
confidence: 99%